A Systematic Review of the Ethnomamatics Characteristics in Indonesian Culture - Sopamena, Patma; Sehuwaky, Nurlaila; Kaliky, Syafruddin; Juhaevah, Fahruh; Litiloly, Hasdi (Jurnal Pendidikan MIPA, 2022)
Based on the differences and similarities of mathematical cultural roots in Indonesia, it is necessary to describe its characteristics and indicators. This article systematically reviews indicators in the roots of mathematical culture in Indonesia based on previous research guided by Prisma's statements. Metadata was analyzed using open coding and re-encoded through axial and selective coding to form ethnomathematics characteristics in Indonesian culture. The results showed that ethnomathematics in Indonesian culture has four characteristics, including 1) Using integer operations, patterns and number bases, residual theorem, modulo, and unity, Kubik, determination of surface area in starting development activities and determining seasonal systems; 2) Using the concept of geometric transformation in making Batik motifs and traditional houses; 3) Conducting games by exploring arithmetic and probabilities, ideas, and mathematical practices; and 4) Using human body size as a measuring tool in starting a development activity and planting land. Keywords: systematic review, Ethnomamatics, characteristics, Indonesian culture. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1195-1204